Determination of estrogenic mycotoxins in environmental water samples by low-toxicity dispersive liquid-liquid microextraction and liquid chromatography-tandem mass spectrometry - Emidio, Elissandro Soares [UNESP]; Silva, Claudia Pereira da [UNESP]; Rodrigues de Marchi, Mary Rosa [UNESP] (Elsevier B.V., 2015)
A novel, simple, rapid and eco-friendly method based on dispersive liquid-liquid microextraction using a bromosolvent was developed to determine six estrogenic mycotoxins (zearalenone, zearalanone, alpha-zearalanol, beta-zearalanol, alpha-zearalenol and beta-zearalenol) in water samples by liquid chromatography-electrospray ionization tandem mass spectrometry in the negative mode (LC-ESI-MS/MS). The optimal conditions for this method include the use of 100 mu L bromocyclohexane as an extraction solvent (using a non-dispersion solvent), 10 mL of aqueous sample (adjusted to pH 4), a vortex extraction time of 2 min, centrifugation for 10 min at 3500 rpm and no ionic strength adjustment. The calibration function was linear and was verified by applying the Mandel fitting test with a 95% confidence level. No matrix effect was observed. According to the relative standard deviations (RSDs), the precision was better than 13% for the repeatability and intermediate precision. The average recoveries of the spiked compounds ranged from 81 to 118%. The method limits of detection (LOD) and quantification (LOQ) considering a 125-fold pre-concentration step were 4-20 and 8-40 ng L-1, respectively. Next, the method was applied to the analysis of the environmental aqueous samples, demonstrating the presence of beta-zearalanol and zearalanone in the river water samples. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Estrogenic mycotoxins; Bromosolvents; Dispersive liquid-liquid microextraction; Water samples; LC-MS/MS